MASCULINITY IN JESMINDER BHAMRA AS THE MAIN CHARACTER OF BEND IT LIKE BECKHAM FILM - Fitriani Fitriani; Satyawati Surya; Anjar Dwi Astuti (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This study aimed to reveal the masculinity traits in Jesminder Bhamra of Bend It Like Beckham film based on Bem’s theory and to find out the characteristics of Jesminder Bhamra as portrayed in the film by using Reaske’s theory of characterization. This study used qualitative design with content analysis approach. The source of data in this study was Bend It Like Beckham film script, while the data consisted of dialogues, utterances, and scenes related to Jesminder Bhamra’s masculinity traits. From the total twenty indicators of masculinity traits, Jesminder Bhamra showed to have eight kinds of masculinity traits such as aggresive, ambitious, analytical, athletic, competitive, defends own belief, has leadership ability, and masculine. Jesminder Bhamra character was characterized through the five tools of characterization from the six tools in Reaske’s theory; they are appearance, aside and soliloquy, dialogues, hidden narration, and actions.